2020
DOI: 10.2478/jcbtp-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Does Bank Competition Enhance or Hinder Financial Stability? Evidence from Indian Banking

Abstract: The primary purpose of this paper is to empirically investigate the impact of bank competition on financial stability in India. We use a dynamic panel model to examine whether an increase in bank competition hindrances financial stability of commercial banks in India over the period 1996 to 2016. Findings reveal that in India, a higher degree of bank competition is positively associated with the prevalence of non-performing loans. Additionally, the positive impact of the Lerner index on Z-score lends support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Therefore, our study supports the viewpoints of both competition stability and competition fragility, and our results are consistent with Rakshit and Bardhan (2020), who argues that both the competition stability and competition fragility views can coexist in a single banking system like India.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our study supports the viewpoints of both competition stability and competition fragility, and our results are consistent with Rakshit and Bardhan (2020), who argues that both the competition stability and competition fragility views can coexist in a single banking system like India.…”
Section: Discussionsupporting
confidence: 91%
“…Nain et al 92020) found uncertainty influences the effectiveness of monetary policy shock. Rakshit et al (2020) reveal that in India, a higher degree of bank competition is positively as sociated with the prevalence of non-performing loans. Okpamen et al (2020) said firms needed to encourage adequate interlocking members who have diverse professional training, high social net worth and experience (experience hypothesis) to positively influence effective management and financial performance of listed firms in Nigeria.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 98%
“…Since the inception of financial liberalization in 1991, India's banking industry has undergone several phases of financial reforms. The reform measures primarily promoted bank competition (Bhattacharya and Das, 2003;Prasad and Ghosh, 2007;Li et al, 2019;Rakshit and Bardhan, 2020a), enhanced stability (Dhal et al, 2011;Sarkar and Sensarma, 2016;Rakshit and Bardhan, 2020b), improved efficiency (Ataullah and Le, 2006;Ray and Das, 2010;Zhao et al, 2010;Gulati and Kumar, 2016) and increased profitability (Seenaiah et al, 2015;Ahamed, 2017) to cater to the needs of higher economic growth. The liberalization policies pursued to increase the functional autonomy at the micro, and Empirical evidence from Indian banking 1867 macro-level remarkably strengthened the health of Indian banking (Das and Ghosh, 2009).…”
Section: Introductionmentioning
confidence: 99%